Study on the pelletizing of sulfate residue with magnetite concentrate in grate-kiln system - Shufeng Y.; Jingshe L.; Yan-Qi S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The experiment on the feasibility of pelletizing with magnetite concentrate and the wasted sulfate residue was carried out, to research the performance of pellet in grate-kiln system and simulate the grate-kiln pelletizing process in the micro-pellet roasting simulation system in laboratory, and the process experiments on preheating and roasting sections were conducted. The results show that in order to obtain pellet with good performance and the magnetite concentrate should be over 20 in mass percent, the suitable pelletizing time is about 10 min and moisture is around 12.5%. Also, according to the process parameters of drying and preheating sections obtained from experiment, it will be successful to use magnetite concentrate and the wasted sulfate residue for pelletizing, which exploits a new way for the use of sulfate residue.